PENINGKATAN KELEMBAGAAN KARANGTARUNA DI DESA CIJEUNGJING KECAMATAN CIJEUNGJING KABUPATEN CIAMIS - Syahril Sidqi Abdillah; Rimba; Kiki Endah; Eva Pujasari; Hilya Auliya; M. Vikri Aditya (CV SWA Anugerah, 2024)
The purpose of this practicum is to find out the extent of the empowerment of the Bina Muda Youth Organization in Cijeungjing Village, Cijeungjing District, Ciamis Regency. The qualitative approach method is the type of research used. The type of research used. the research focuses on the purpose of empowerment, empowerment based on the Regulation of the Minister of Social Affairs Number 23 of 2013, which has several stages: preparation for empowerment, implementation, and subsequent utilization. The development of youth activities involves a number of difficult procedures or stages, such as coordinating the work programs of the Village and the Youth Organization of Cijeungjing Village.